Developing a novel calcium magnesium silicate/graphene oxide incorporated silk fibroin porous scaffold with enhanced osteogenesis, angiogenesis and inhibited osteoclastogenesis. (1st May 2022) - Wu, Tingting; Li, Binglin; Huang, Wenhan; Zeng, Xianli; Shi, YiWan; Lin, Zefeng; Lin, Chengxiong; Xu, Weikang; Xia, Hong; Zhang, Tao
Abstract: Recently, biofunctional ions (Mg 2+, Si 4+, etc) and graphene derivatives are proved to be promising in stimulating bone formation. In this study, a novel inorganic/organic composite porous scaffold based on silk fibroin (SF), graphene oxide (GO), and calcium magnesium silicate (CMS) was developed for bone repair. The porous scaffolds obtained by lyophilization showed a little difference in pore structure while GO and CMS displayed a good interaction with SF matrix. The addition of CMS with good mineralization potential and sustainedly release ability of biofunctional ions (Ca 2+, Mg 2+ and Si 4+ ) increased the strength of SF scaffolds a little and facilitated the osteogenic differentiation of bone mesenchymal stem cells (BMSCs) by upregulating bone formation-related genes (ALP, COL1, OC and Runx2). The further incorporation of GO in SF scaffolds enhanced the compressive strength and water retention, and also remarkably promoted the osteogenic differentiation of BMSCs. Besides, the angiogenesis of human umbilical vein endothelial cells was significantly promoted by CMS/GO/SF scaffold extract through the upregulation of angiogenesis genes (eNOs and bFGF). Moreover, the osteoclastic formation ability of RAW264.7 cells was suppressed by the released ions from CMS/GO/SF scaffold through the down-regulation of CAK, MMP9 and TRAP. The promoted osteogenesis, angiogenesis and inhibited osteoclastogenesis functions of CMS/GO/SF composite scaffold may enable it as a novel therapy for bone repair and regeneration.